Profile of cryptobrachytone C accumulation in Cryptocarya pulchrinervia leaves using MALDI-MSI - Jujun Ratnasari; Rizkita Rachmi Esyanti; Marselina Irasonia Tan; Lia Dewi Juliawaty; Shuichi Shimma (Society for Indonesian Biodiversity, 2021)
Abstract. Ratnasari J, Esyanti RR, Tan MI, Juliawaty LD, Shimma S. 2021. Profile of cryptobrachytone C accumulation in Cryptocarya pulchrinervia leaves using MALDI-MSI. Biodiversitas 22: 1172-1178. Cryptobrachytone C is an active compound isolated from leaves of Cryptocarya pulchrinervia, an indigenous plant from Indonesia. Cryptobrachytone C is cytotoxic against P388 leukemia cancer cell lines. A profile of cryptobrachytone C accumulation in leaves based on physiological age is necessary to study cryptobrachytone C production in the plant since it has anticancer potential. In situ profiling of cryptobrachytone C accumulation in leaves was carried out by imaging techniques using matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI). The cryptobrachytone C ionization efficiency was carried out by derivatization using Girard-T reagent and coating with ?-cyano-4-hydroxycinnamic acid (?-CHCA) matrix. Scanned leaves show higher accumulation intensity in the second leaf. Quantitative accumulation profiling was conducted using GC-MS, where the highest amount of cryptobrachytone C was on the second leaf at 87.07 ± 47.21 mg. This showed that the most effective isolation of cryptobrachytone C would be obtained from young leaves of Cryptocarya pulchrinervia. This profile would play a role in cryptobrachytone C production in-situ or ex-situ using tissue culture.